Minimasi Kelebihan dan Kekurangan Berat pada Proses Pengisian Tepung Bumbu Kemasan 40 Gram - Andira Taslim; Rintih Kurniawati (JIE Scientific Journal on Research and Application of Industrial System, 2019)
Quality is an assessment of products that are in accordance with customer specifications and relate to the level of customer satisfaction. Quality is one of the factors that influence the competitiveness of a product in the market. One indicator of the quality of a product is the presence or absence of defects (defects) of the products produced. In this study the DMAIC method was applied to solve the problem in the process of filling the 40 gram seasoning flour packaging on a single line machine at PT XYZ. The use of the DMAIC method aims to reduce defects due to the instability of the seasoning flour filling process which causes a mismatch of product weights to the specified standards. The improvement phase includes setting the machine by adjusting the distance between the cup and scraper on a single line machine and by increasing the number of sampling. Sampling the weight of the product that was previously only once every hour by the QC operator, added to the sampling every half hour by the production operator and once an hour is still carried out by the QC operator.